PENGARUH QUALITY OF WORK LIFE DAN PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP PERILAKU KERJA INOVATIF DOSEN YANG DIMEDIASI KOMITMEN ORGANISASI (Studi pada Dosen Politeknik Pusmanu Pekalongan) - Elshifa, Aria; Dwi Anjarini, Ari; Jamaludin Kharis, Aghus (Economicus, 2019)
The purpose of this study is to determine and analyze the effect of quality of work life and the use of information technology on organizational commitment. Knowing and analyzing the effect of quality of work life, use of information technology and organizational commitment to innovative work behavior of lecturers. The population in this study were 34 lecturers at Pusmanu Pekalongan Polytechnic. The results of the study can be concluded as follows: quality of work life and the use of information technology have a positive and significant effect on organizational commitment of Pusmanu Pekalongan Polytechnic lecturers. Quality of work life, the use of information technology and organizational commitment have a positive and significant effect on the innovative work behavior of Pusmanu Pekalongan Polytechnic lecturers. Organizational commitment as a variable that intervenes the influence of quality of work life and the use of technology on innovative work behavior of Pusmanu Pekalongan Polytechnic lecturers.